The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.1111/j.1748-5827.1995.tb02921.x
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic insulin‐secreting carcinoma in a dog: Fructosamine for determining persistent hypoglycaemia

Abstract: A five-year-old intact male rottweiler was presented with a history of episodic weakness and mild-generalised seizures. A tentative diagnosis of an insulin-secreting tumour in the pancreas was made based on fasting hypoglycaemia with concomitant hyperinsulinaemia and a subnormal fructosamine value. The diagnosis was confirmed by exploratory coeliotomy, intravenous infusion of methylene blue, histopathology and immuno-histochemical analysis of suspected neoplastic tissue. Fructosamine assays are traditionally u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…30,31 Fructosamine concentration can be used as an indicator of chronic hypoglycemia as this parameter reflects the blood glucose concentrations over the previous 1-2 wk. [30][31][32] Initially used to evaluate chronic hyperglycemia in dogs with diabetes mellitus, several studies have reported that dogs with insulinomas do have significantly lower fructosamine concentrations than normal. [30][31][32] The turnaround time of this test varies between laboratories, but may take up to several days.…”
Section: Laboratory Datamentioning
confidence: 99%
“…30,31 Fructosamine concentration can be used as an indicator of chronic hypoglycemia as this parameter reflects the blood glucose concentrations over the previous 1-2 wk. [30][31][32] Initially used to evaluate chronic hyperglycemia in dogs with diabetes mellitus, several studies have reported that dogs with insulinomas do have significantly lower fructosamine concentrations than normal. [30][31][32] The turnaround time of this test varies between laboratories, but may take up to several days.…”
Section: Laboratory Datamentioning
confidence: 99%
“…107 This may be due to intermittent cortisol-induced peripheral insulin resistance while at the veterinary clinic; blood glucose concentration is in the normoglycemic range during these visits, yet is usually in the hypoglycemic range otherwise, resulting in decreased formation of fructosamine. 107 This may be due to intermittent cortisol-induced peripheral insulin resistance while at the veterinary clinic; blood glucose concentration is in the normoglycemic range during these visits, yet is usually in the hypoglycemic range otherwise, resulting in decreased formation of fructosamine.…”
Section: Hypofructosaminemiamentioning
confidence: 99%
“…Serum fructosamine concentrations may be below normal limits in a dog that has had frequent periods of hypoglycemia in the prior 2 weeks. 36 Normal fasting serum IRI levels in dogs are less than 30 μU/ml. The glucose/insulin ratio is generally sufficient for a diagnosis.…”
Section: Beta-cell Tumors (Insulinoma)mentioning
confidence: 98%